Firms as Financial Intermediaries : Evidence from Trade Credit Data - Demirguc-Kunt, Asli; Maksimovic, Vojislav (World Bank, Washington, DC, 2014)
The authors argue that non-financial firms act as intermediaries, by channeling short-term funds from the financial institutions in an economy, to their best use. Non-financial firms act in this way because they may have a comparative advantage in exploiting informal means of ensuring that borrowers repay. These considerations suggest that to optimally exploit their advantage in providing trade credit to some classes of borrowers, firms should obtain external financing from financial intermediaries, and markets, when this is efficient. Thus the existence of a large banking system is consistent with these considerations. Using firm-level data for thirty nine countries, the authors compute turnovers in payables, and receivables, and examine how they differ across financial systems. They find that the development level of a country's legal infrastructure, and banking system predicts the use of trade credit. Firms' use of bank debt is higher relative to their use of trade credit in countries with efficient legal systems. Bur firms in countries with large, privately owned banking systems, offer more financing to their customers, and take more financing from them. The authors' findings suggest that trade credit is a complement to lending by financial intermediaries, and should not be viewed by policymakers as a substitute.